Life skills development in young high-level athletes - Jørgensen, H. (Department of Coaching and Psychology, Norwegian School of Sport Sciences, 2018)
The purpose of the current study was to examine the development of life skills through sport participation among young high-level athletes who are part of a talent development program. Life skills are identified as an outcome of positive youth development (PYD; Holt, 2016), which is a commonly used framework in youth sport research with a focus on using sport to develop well-rounded individuals (Fraser-Thomas, Côté, & Deakin, 2005). Talent development in sport, on the other hand, tends to focus on the development of better athletes. However, researchers have suggested that PYD and talent development are not necessarily mutually exclusive aspects of high-level youth sports (Strachan, Fraser-Thomas, & Nelson-Ferguson, 2016). That is, talent development programs can achieve PYD outcomes if an inclusive approach is present, emphasizing the teaching of both athletic and life skills (Harwood & Johnston, 2016).